2014
DOI: 10.1371/journal.pone.0085942
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of TGF-β Signaling Pathway and Prognosis of Pancreatic Cancer

Abstract: BackgroundTransforming growth factor (TGF)-β signaling pathway, may act both as a tumor suppressor and as a tumor promoter in pancreatic cancer, depending on tumor stage and cellular context. TGF-β pathway has been under intensive investigation as a potential therapeutic target in the treatment of cancer. We hypothesized a correlation between TGF-βR2/SMAD4 expression in the tumor, plasma TGF-β1 ligand level, genetic variation in TGF-B pathway and prognosis of pancreatic cancer.MethodWe examined TGF-βR2 and SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 30 publications
3
76
0
1
Order By: Relevance
“…High levels of TGFβ in patients with pancreatic cancers is associated with poor prognosis 42 . Anti-TGFβ compounds have shown efficacy in preclinical and clinical studies 43,44 , suppressing liver metastasis by acting on both incoming tumor cells and the liver microenvironment 45 .…”
Section: Discussionmentioning
confidence: 99%
“…High levels of TGFβ in patients with pancreatic cancers is associated with poor prognosis 42 . Anti-TGFβ compounds have shown efficacy in preclinical and clinical studies 43,44 , suppressing liver metastasis by acting on both incoming tumor cells and the liver microenvironment 45 .…”
Section: Discussionmentioning
confidence: 99%
“…A rapid autopsy study from Johns Hopkins showed a correlation between the loss of SMAD4/DPC4 expression and greater propensity for metastatic disease 8. Within the same pathway, high transforming growth factor-β1 plasma levels, the SMAD4 single-nucleotide polymorphism rs11354983, and high transforming growth factor-βR2/SMAD4 expression are similarly correlated with poor outcomes 35. SMAD4 is a stratification factor, alongside CA19-9 levels, in ongoing cooperative group studies 36…”
Section: Future Directionsmentioning
confidence: 99%
“…TGF-β ligand expression is elevated in PDAC, and patients with high levels of TGF-β1 ligand in their serum have a significantly worse prognosis (46). However, mutations that inactive the canonical TGF-β-Smad signaling pathway are common in PDAC, with around 55% of PDAC patients having inactivating mutations in SMAD4 (47).…”
Section: Tgf-β Signaling Induces Cyr61 Expression In Pscs In the Pdacmentioning
confidence: 99%